«¡Publish or perish!» On the need for a critical theory of the university - Fleitas González, Martín; Aranco Bagnasco, Agustín; Correa Parodi, Facundo (CIAN-Revista de Historia de las Universidades, 2025)
The article addresses some problems associated with hyperindexation that regenerate contemporary university and academic dynamics during the production, appropriation and supervision of knowledge, through the phenomenon of papers: these convey a heterogeneous set of forces (corporatization of universities, commercialization of their curricula, emptying of public funds, monopolization of publishers) that give rise to a huge number of adversities for the epistemic credibility of the university. By virtue of that, the article systematizes the most important objections that have been accumulating in recent times around the production of knowledge via papers, to then point out the subjective cost that this way of generating knowledge entails for researchers in terms of job and psychological precariousness. Based on the description of the general framework of the forces that are juxtaposed on the backs of the paper, the article suggests the need to develop a “critical theory of the university” that can appropriate and reflexively reorient its challenges, indicating for this a set of ethical and political recommendations to take into account during the generation, appropriation and supervision of knowledge.